IDX Carbon dan Kinerja Keuangan: Dampak Pembelian Karbon terhadap Profitabilitas dan Persepsi Investor - Asiah, Nur; Agus Munandar (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2025)
The specific objective of this research is to analyze carbon purchases on a company's financial performance, especially in the context of profitability and investor perception. The main focus of this study is companies listed on the Indonesia Stock Exchange, the banking sector that made their first carbon purchases, namely: PT Bank CIMB Niaga Tbk, PT Bank Mandiri Tbk, and PT Bank Central Asia Tbk (BCA). The method used in this study is descriptive analysis to describe the relationship between existing variables. The results of the study indicate that although there are variations in carbon purchases among these companies, ROA tends to increase steadily, while EPS decreases, with a peak occurring in a certain quarter. Although carbon purchases can increase operating costs in the short term, these companies are able to maintain their financial performance. This suggests that policies involving carbon emission reductions can have a long-term positive impact on profitability and investor perception, although their direct effects on EPS can be volatile. This study suggests that companies should pay more attention to carbon purchase management and sustainable sustainability strategies to increase investor confidence and ensure sustainable profitability. Further research is suggested with a quantitative approach and panel model analysis can provide deeper insights into the effect of desire policies on financial performance in the long term.